Immune boosting and anti-influenza effects of an Unani decoction in influenza like illness and COVID-19 like epidemics: a rationale approach - Ansari, Athar P.; N., Zaheer Ahmed; Rather, Shameem A.; Rafeeqi, Towseef A.; Beigh, Basharat Saleem (International Journal of Research in Medical Sciences, 2020)
The Unani system of medicine is one of the traditional systems of medicine practised since centuries in many parts of the world including India. At a time when the coronavirus disease 2019 (COVID-19) pandemic is still raging across the globe and there is still no appreciable satisfactory management available with vaccination being the only panacea in the near future, unani medicine chiefly composed of herbal drugs is replete with many classical references for the management of influenza like illness and COVID-19 like epidemics. In Unani medicine, nazla-i-wabāi is referred as influenza for which a decoction containing Behidana (Cydonia oblonga), Unnab (Ziziphus jujuba) and Sapistan (Cordia myxa) are recommended to relieve the clinical features of nazla-i-wabāi and other COVID-19 like epidemics. All the three ingredients of this formulation are also individually used for the treatment of sore throat, cough, septicaemia, fever, dyspnoea, pharyngitis, chest pain etc. Certain scientific studies have validated various pharmacological actions of these drugs as claimed by unani physicians. A concerted rational approach has been attempted to highlight the effect of the unani decoction as to its immune boosting property both as prophylactic and therapeutic use in the treatment of influenza like illness and COVID-19 like epidemics in the light of ancient Unani classics and recent scientific studies.